Response of Photosynthesis and Chlorophyll Fluorescence to Nitrogen Changes in Rice with Different Nitrogen Use Efficiencies - Zexin Qi; Chen Xu; Rui Tang; Qiang Zhang; Wenzheng Sun; Chenglong Guan; Ye Wang; Mengru Zhang; Jiale Ding; Yuankai Zhang; Hong Yang; Ying Yang; et al. (Plants)
Nitrogen is a key element in promoting crop growth and development and improving photosynthesis. This study aimed to study the response of two rice genotypes to the restoration of N supply after varying periods of N deficiency. We used the low-nitrogen-tolerant rice Jijing 88 (JJ 88) and the nitrogen-sensitive rice variety Xinong 999 (XN 999) as test materials. The results of this study indicated that, compared to XN 999, JJ 88 has a higher content of the photosynthetic pigments. Photosynthesis in JJ 88 has strong adaptability under low-nitrogen conditions. Upon an increase in the nitrogen supply level, the maximum regeneration rate of ribulose biphosphate (RuBP, Jmax) and the maximum carboxylation rate of RuBP (Vcmax) in JJ 88 showed a relatively large increase. The chlorophyll fluorescence parameters, including the effective quantum yield of photosystem II (ΦPSII), the efficiency of excitation capture by open PSII centers (Fv′/Fm′), photochemical fluorescence quenching (qP), and the electron transfer rate (ETR) decreased slightly, while the non-photochemical fluorescence quenching (NPQ) increased slightly. Under low-nitrogen conditions, low-nitrogen-tolerant rice varieties maintain reasonable growth during the seedling stage. With an increase in the nitrogen supply level, the dry matter accumulation, photosynthetic pigment content, photosynthesis, and electron transfer ability of plants improve, but not to normal nitrogen supply levels. However, compared with XN 999, JJ 88 has a more proactive recovery ability. The research results provide valuable guidance for the breeding of nitrogen-efficient rice varieties and nitrogen fertilizer management.